The legal situation: the place and importance in the mechanism of implementation of administrative coercion by the bodies of internal affairs - Telyatitskaya, Tatiana V.; Lubenkov, Alexander V. (Journal of the Belarusian State University. Law, 2019)
In the context of the search for new approaches to the study of legal reality from the perspective of the dynamics of the urgency and practical significance of the development of the «legal situation» category. Grounded theoretical principles that reveal the essence of the place and importance of the legal situation as an element of the mechanism of realization of the internal affairs bodies of administrative coercive measures. They allow you to supplement the missing knowledge in the field of administrative law realization theory. The main factors determining the quality and effectiveness of implementation by the internal affairs bodies administrative-legal means of coercion in ekzistantaj legal sea experiences of, in aggregate, are the level of legal culture and law-openimage actors in it are, the degree of stress of profession and professional readiness of the bodies of internal affairs.
Keywords: administrative enforcement; the mechanism of implementation of administrative coercion by the bodies of internal affairs; the legal situation